2004
DOI: 10.1097/01.wcb.0000106012.33322.a2
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Gene Expression Analysis for Induced Ischemic Tolerance and Delayed Neuronal Death following Transient Global Ischemia in Rats

Abstract: Summary:Genome-wide gene expression analysis of the hippocampal CA1 region was conducted in a rat global ischemia model for delayed neuronal death and induced ischemic tolerance using an oligonucleotide-based DNA microarray containing 8,799 probes. The results showed that expression levels of 246 transcripts were increased and 213 were decreased following ischemia, corresponding to 5.1% of the represented probe sets. These changes were divided into seven expression clusters using hierarchical cluster analysis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
47
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 74 publications
8
47
0
Order By: Relevance
“…In particular, cells in the penumbra display a complex response to ischemia, including selectively increased mRNA levels of genes associated with stress, apoptosis, transcription, and inflammation. More than 8000 genes associated with transient global ischemia in rats were analyzed by the DNA microarray technique (Lockhart and Winzeler, 2000) to show that expression levels of 246 transcripts were increased and 213 were decreased after ischemia (Kawahara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, cells in the penumbra display a complex response to ischemia, including selectively increased mRNA levels of genes associated with stress, apoptosis, transcription, and inflammation. More than 8000 genes associated with transient global ischemia in rats were analyzed by the DNA microarray technique (Lockhart and Winzeler, 2000) to show that expression levels of 246 transcripts were increased and 213 were decreased after ischemia (Kawahara et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…C2H2-ZFPs were shown to be required for key cell processes, including transcriptional regulation, development, pathogen defense and stress responses. ZFPs were shown to be upregulated by IPC (15,19), although the role of ZFPs in cerebral ischemia is controversial. For example, EGR-1, which is upregulated following focal and global ischemia, was shown to induce apoptotic cell death in certain studies (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Gene microarray and proteomics analyses suggested that the induction of endogenous neuroprotective genes plays an important role in the acquisition of ischemic tolerance (13)(14)(15). C2H2 zinc-finger proteins (ZFPs) constitute the largest family of transcription factors in higher eukaryotes (16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…our expectation was based on studies dealing with neuroprotection trough preconditioning (a short ischemia preceding a long one), that reported quite a high decrease of the c-fos expression after preconditioning (Yoneda et al 1998;Truettner et al 2002;Nyitrai et al 2005 However, the function of c-Fos in neurodegeneration or neuroprotection is controversial. according to some articles, c-Fos plays an important role in the stimulation of neuroprotective mechanisms (Cho et al 2001;Jiang et al 2001;kawahara et al 2004), whereas other studies emphasize its role in neurodegenerative processes (Zablocka et al 2003). The dentate gyrus is quite a resistant area to the transient brain ischemia, although the c-fos expression following ischemia is very high.…”
Section: Discussionmentioning
confidence: 99%